If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 6 = -6(x + -1) Reorder the terms: 6 + -7x = -6(x + -1) Reorder the terms: 6 + -7x = -6(-1 + x) 6 + -7x = (-1 * -6 + x * -6) 6 + -7x = (6 + -6x) Add '-6' to each side of the equation. 6 + -6 + -7x = 6 + -6 + -6x Combine like terms: 6 + -6 = 0 0 + -7x = 6 + -6 + -6x -7x = 6 + -6 + -6x Combine like terms: 6 + -6 = 0 -7x = 0 + -6x -7x = -6x Solving -7x = -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -7x + 6x = -6x + 6x Combine like terms: -7x + 6x = -1x -1x = -6x + 6x Combine like terms: -6x + 6x = 0 -1x = 0 Divide each side by '-1'. x = 0 Simplifying x = 0
| -.4x+2x=.5x+9.5 | | 8(6x-1)=23(2x-2) | | -7x+2=5(2-x) | | 5(2a-3)-6(a+2)=-17 | | (x-5)/6 | | 2x^3y(x^3-4xy-1)= | | 5(2x-1)+4x=10-x | | x+12x-68=10 | | 4x^2+27xy+18y^2=0 | | -2x+30=68 | | 3x+.25x-2.5=7 | | -0.33+2m=-.20 | | x(x-16)=17 | | 84x2/7 | | -2/7y=8 | | 5x-3x+4=5x-x | | 8y^5(9y)= | | 8(x+1)-7=-6 | | x^2/49-1=0 | | x-30=102 | | .5y+8=-12 | | -0.8y=-3.2 | | cos=9 | | 2x-25(5x-15)=6 | | 4x+2x-10=180 | | sen(2x)-senx=0 | | 5y+7y=4 | | -14-(-40)=x/11 | | 2(b-5)=4(b+2)-12 | | 8x+1-9x=9-(x-8) | | 0.60x+0.50(120)=0.30(128) | | 4y+39=-3y-10 |